Acute toxicity of methyl isocyanate: a preliminary study of the dose response for eye and other effects. Issue 12 (December 1985) - Salmon, A G; Kerr Muir, M; Andersson, N
Abstract : Acute toxic effects of methyl isocyanate in the rat were determined for two hour exposures to concentrations in the range 11 ppm (very slight effect) to 65 ppm (lethality: pulmonary oedema). Changes in the eye, lungs, and behaviour were noted. Eye changes were confined to erosions of the corneal epithelium and were most severe at intermediate levels of exposure. A comparison was made of the effects noted in rats with reported effects on survivors of the Bhopal disaster. Urinary thiocyanate concentrations in exposed rats were found to be reduced relative to control values.